KUALITAS PELAYANAN PENDIDIKAN ANAK BINAAN DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) KLAS 1 KUTOARJO KABUPATEN PURWOREJO - Riska Wirawan; Ida Hayu Dwimawanti (Magister Administrasi Publik, FISIP, 2019)
Analysis of the quality of educational services is very important for progress of educational organization to more improved service. This research aimed to analyse the quality of education equality program paket C in the LPKA Clas 1 Kutoarjo, and for look resistor and support factors in realizing quality educational service of equality program paket C in the LPKA Clas 1 Kutoarjo To obtain an answer from its intended destination, the research approach used is qualitative by using five dimensions of service quality that is tangible, reliability, responsiveness, assurance and empathy, and five factors inhibiting and supporting the quality of service that is a factor of awareness of employees, agencies/organizations, capacity/skills officer, employee interaction, climate and labor relations.The results showed that the quality of education services in equality Packet program c in LPKA Class 1 Kutoarjo is good enough, an outline of some of the dimensions of service quality are met such as educational facilities are available, atmosphere learning cozy, a place of education accessible, employee attitudes is set in the guidelines the treatment of children in LPKA educational requirements and procedures that apply to the conditions, a good employer responses concerned with students, conduct service management system a good education, education fair and non discriminate. Although there are some things that still has shortcomings such as the number of teaching staff, teacher attendance rates and other supporting facilities. Furthermore, to assurance a time education is still not good, the certainty of a teacher who can not be present on schedule, inhibits the teaching and learning activities. So the problem assurance a time education is still needing repair so that can give quality education service. As for resistor factor od service quality Education LPKA That provision factor Time from Organization And Officers ability factor, Few Obstacles from employe Interaction factor whit Children's. While Namely supports factor Awareness factors apparatus, employee interaction, and climate factorsworking relationship.